2014
DOI: 10.1021/es403582f
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation with DistinctDehalobacterStrains Achieves Chloroform Detoxification in Microcosms

Abstract: Chloroform (CF) is a widespread groundwater contaminant not susceptible to aerobic degradation. Under anoxic conditions, CF can undergo abiotic and cometabolic transformation but detoxification is generally not achieved. The recent discovery of distinct Dehalobacter strains that respire CF to dichloromethane (DCM) and ferment DCM to nonchlorinated products promises that bioremediation of CF plumes is feasible. To track both strains, 16S rRNA gene-based qPCR assays specific for either Dehalobacter strain were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…The feasibility of bioaugmentation for chloroform and DCM detoxification has been demonstrated (Justicia‐Leon et al ., ), and the findings reported here highlight that chloroform remediation can be sustained without biostimulation (i.e., electron donor addition) because the degradation of the daughter product DCM generates the H 2 required for chloroform reductive dechlorination. A logical extension of this concept is that DCM serves as an indirect electron donor (i.e., a source of H 2 and acetate) to support other reductive processes such as nitrate reduction, organohalide respiration, iron reduction, sulfate reduction, methanogenesis and reductive acetogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of bioaugmentation for chloroform and DCM detoxification has been demonstrated (Justicia‐Leon et al ., ), and the findings reported here highlight that chloroform remediation can be sustained without biostimulation (i.e., electron donor addition) because the degradation of the daughter product DCM generates the H 2 required for chloroform reductive dechlorination. A logical extension of this concept is that DCM serves as an indirect electron donor (i.e., a source of H 2 and acetate) to support other reductive processes such as nitrate reduction, organohalide respiration, iron reduction, sulfate reduction, methanogenesis and reductive acetogenesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dehalobacter species are regarded as specialist dehalogenating bacteria able to use a wide variety of aliphatic and aromatic organochlorines as terminal electron acceptors (Nelson et al, 2014), the exceptions being Dehalobacter lineages shown to ferment DCM to acetate and hydrogen (Lee et al, 2012;Justicia-Leon et al, 2014). Strain UNSWDHB could not ferment DCM (0.2 mM) when supplied as the sole source of organic carbon and electrons after 4 weeks of observation.…”
Section: Electron Acceptor Repertoire and Growth Yieldsmentioning
confidence: 99%
“…Moreover, microbial communities comprising both TCM respiring and dichloromethane (DCM) fermenting bacteria have shown that complete TCM dechlorination is a feasible bioaugmentation strategy. (Lee et al ., ; Justicia‐Leon et al ., )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT and CF inhibit mutual biodegradation (Grostern et al, 2010;Lima and Sleep, 2010;Justicia-Leon et al, 2014) and also microbial respiration of chlorinated ethanes and ethenes by Dehalococcoides and Desulfitobacterium species (Bagley et al, 2000;Weathers and Parkin, 2000;Maymó-Gatell et al, 2001;Duhamel et al, 2002;Futagami et al, 2006Futagami et al, , 2013, and this hinders natural attenuation and bioremediation strategies in complex sites impacted by mixtures of chlorinated compounds.…”
Section: Introductionmentioning
confidence: 99%